Effects of Exercise on Hypertension From Cells to Physiological Systems - Pescatello, Linda S. (Molecular and Translational Medicine, 2015)
This text explores the state-of-the-art effects of exercise on blood pressure among adults with hypertension in addition to many of the possible mechanisms underlying essential hypertension in humans. The book contains chapters by distinguished experts on the effects of exercise on physiological systems known to be involved in hypertension development and maintenance as well as less well known aspects of hypertension such as exercise effects on the 24-hour ambulatory blood pressure profile, and inflammation and oxidative stress as they relate to hypertension. An emerging area, the effects of resistance exercise training on blood pressure is also covered. A unique aspect of the book is that it covers the effects of exercise mimetics on vascular cell adaptations in order to begin to elucidate some of the cellular mechanisms that may underlie blood pressure reductions with exercise training. The text also contains a chapter on the interactive effects of genes and exercise on blood pressure. Effects of Exercise on Hypertension: From Cells to Physiological Systems will be of great value to professional individuals in cardiovascular medicine, the cardiovascular sciences, allied health care professionals, and medical and graduate students in the cardiovascular sciences and medicine.